FANRPAN 2009 Annual Regional Multi-Stakeholder Policy Dialogue: Summary of Proceedings - Takavarasha, Tobias (FANRPAN, 2009)
This dialogue brought together researched case studies from different countries on the “true contribution of agriculture to economic growth and poverty in southern Africa” – based on the various forward and backward linkages...